2005
DOI: 10.1590/s0100-40422005000300026
|View full text |Cite
|
Sign up to set email alerts
|

Plantas medicinais: cura segura?

Abstract: This paper reviews the recent literature on synergism, adulteration and risks of using medicinal plants. The use of copaiba and sacaca plants as well as their adulteration and side effects, are also described. In addition, the new regulations on phytotherapeutic registration in Brazil and Europe are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
75
0
145

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(222 citation statements)
references
References 43 publications
2
75
0
145
Order By: Relevance
“…Brazil has the largest diversified forest reserve on the planet. Many species are used for medicinal purposes with low or no evidence of its properties 11 . The use of medicinal plants is not restricted to rural areas or regions devoided of medical and pharmaceutical care.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil has the largest diversified forest reserve on the planet. Many species are used for medicinal purposes with low or no evidence of its properties 11 . The use of medicinal plants is not restricted to rural areas or regions devoided of medical and pharmaceutical care.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of medicinal plants and the resultant medicines from them may seem to be a little importance compared to that of conventional treatments. However, this is not the case for public health; the toxicity of medicinal plants is a serious problem 2 . The unfavorable effects of plant medicines, of individual products or synergistic action i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, the World Health Organization reported that 65-80% of the population in developing countries depended on medicinal plants as the only form of access to basic health care 9 , and in relation to world population, about 60% makes use of medicinal plants 10 .…”
Section: Introductionmentioning
confidence: 99%